Freedom Institute, Neoliberalism and Phenomenon of Intellectual Trade - Herdi Sahrasad (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2017)
This article highlights the phenomenon of the Freedom Institute, an NGO in which one of the main actors, Rizal Mallarangeng, who acts as if "academic, epistemic, objective and rational" (Intellectuals, BBM and Advertising Freedom Institute, Kompas 3/3), advertises on print newspaper in Jakarta. And the Freedom Institute advertisement, which was founded by Coordinating Minister for Economic Affairs Aburizal Bakrie and his colleagues, has made some people feel "cynical, irritated and frustrated" towards intellectuals who are so easy to "trade knowledge" with all their credibility and capacity. The annoyance and frustration was shown by the Young Kagama Forum in Jakarta (Wednesday, 2/3/2005) which raised it as an issue of “the phenomenon of neoliberalism and intellectual prostitution” in connection with the Freedom Institute advertisement. However, the students and activists who objected to the fuel price hike and were present at the Kagama Youth Forum stated that they were angry and disgusted with why there are a number of well-known intellectuals who so easily involve themselves in neoliberal advertisements that protect the interests of the dominant economic-political power, instead of siding with the oppressed.